CLIL-ised EMI in practice: issues arising. Issue 6 (2nd November 2021) - Moncada-Comas, Balbina; Block, David
ABSTRACT: In the shift to English-medium instruction (EMI) in European higher education, policy often runs ahead of research and curricular decisions are taken independent of evidence regarding their suitability for achieving broader educational goals, which may range from internationalisation as a general strategy to English language learning as a more specific one. Where English language learning is a goal, EMI may be CLIL ised, that is, it is adopted not only for content delivery, but also as a means through which students might improve their English. Drawing on interviews and classroom observations, and employing a Membership Categorisation Analysis methodology, this paper examines how a lecturer in agronomic engineering at a Catalan university experiences CLIL ised EMI. It documents how the lecturer positions himself as a content lecturer and how categories are produced and negotiated in interviews and classroom practices. Among other things, the paper shows that while the lecturer refuses to inhabit an English-language teacher identity, he nonetheless acts in this capacity when he focusses on vocabulary learning through the provision of glossaries and translation. These and other findings point to a more general disjuncture between policy and practice, which, it is argued, needs to be addressed by university administrators and EMI lecturers.